Pengalaman Kesepian pada Mahasiswa Tahun Pertama: Kajian Naratif - Yurni Yurni; Khaila Al Nabila; Amrina Rosada (Universitas Batanghari Jambi, 2024)
When entering the world of college as new students, students experience a transition phase from being high school students. In this new environment, students are expected to be able to develop new social networks, such as new friends. Students who experience problems in this case do not escape the experience of experiencing loneliness. Loneliness is a universal phenomenon experienced by almost everyone, including students. Students in their first year who were the subjects of this research were those who had previously experienced distance learning during Covid-19. The aim of this research is to understand students' experiences of loneliness after becoming students. What is the background to the emergence of feelings of loneliness? determine the initial causes of first-year students' experiences of loneliness. The research subjects were four people, consisting of male and female students, who were obtained using purposive sampling. Subjects are students who have different socio-cultural backgrounds. The research method uses narrative inquiry to reveal students' experiences of loneliness. Individual interviews were conducted to collect data. The research results showed that there were three themes related to the antecedents of students' experiences of loneliness, namely the theme of longing, the theme of losing friends, and the theme of low self-esteem.